2018
DOI: 10.1017/s1463423618000415
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner consultations in primary health care: a case study-based survey of patients’ pre-consultation expectations, and post-consultation satisfaction and enablement

Abstract: Higher levels of patient enablement and satisfaction are not necessarily determined by the time lengths of consultations, and how consultations are conducted may be more important than their time lengths for optimising patient satisfaction and enablement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
2
11
0
3
Order By: Relevance
“…In this study, the CNPs highlighted the luxury of time as one of the cornerstones for the possibilities to provide functional care. The unhurriedness has been noticed as a signi cant enabler for the quality of the client-centered home care services (35,43). Our results are consistent with this and signi ed the possibility of the CNP to settle down and spend more time to nd more contributing solution for the patient's care needs.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the CNPs highlighted the luxury of time as one of the cornerstones for the possibilities to provide functional care. The unhurriedness has been noticed as a signi cant enabler for the quality of the client-centered home care services (35,43). Our results are consistent with this and signi ed the possibility of the CNP to settle down and spend more time to nd more contributing solution for the patient's care needs.…”
Section: Discussionsupporting
confidence: 87%
“…This study indicates that the Australian public have limited awareness of the NP role with only half of the sample having heard of an NP, a finding consistent in contemporary literature [ 22 , 48 ]. This is not surprising given the general publics’ limited understanding of the different categories nurses or levels within nursing groups [ 26 , 49 ], the relatively low number of NPs (approximately 0.5% of the nursing workforce [ 14 , 55 ]) and the fact that the majority of NPs in Australia are predominantly employed in the public sector [ 1 ]. International cross-country comparisons suggest that public exposure to the NP role will also be influenced by the fact that there are only 4.4 NPs per 100,000 population compared with 395 physicians per 100,00 population [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these espoused correlations between extended consultation times and reported patient satisfaction, we found that spending more time during consultations was not a contributing factor to willingness to be see an NP. A recent study found that NPs do not have lengthy consultation times, rather they convey a sense that they are spending more time during consultations [ 55 ]. Indeed, no correlation was found between the length of NP consultations and post-consultation consumer satisfaction or enablement [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The convergent parallel mixed methods case study (Creswell, 2014) was intended to concomitantly scrutinise the communication processes, social interactions and measured outcomes of nurse practitioner consultations using three parallel strands of inquiry: video recordings of nurse practitioner consultations; a validated questionnaire measuring patient expectations, patient satisfaction and patient enablement and also semi-structured individual interviews with selected patient, carer and nurse practitioner participants of the video-recorded consultations. The detailed results of the video recorded and questionnaire components of the study are presented elsewhere in Primary Health Research & Development (Barratt and Thomas, 2018a, 2018b); this paper focuses on reporting the qualitative dimension of the mixed methods case study.…”
Section: Study Design Aim and Research Questionsmentioning
confidence: 99%